PROBLEMATIKA KETERAMPILAN MENULIS DALAM PEMBELAJARAN BAHASA INDONESIA SECARA DARING - Yulianah Prihatin; Raras Hafiidha Sari (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the problems of writing skills in learning Indonesian and offer solutions to solve them. This study uses a qualitative approach with a descriptive method. Data collection techniques using online interview techniques, listen and take notes. In addition, data was also obtained from a questionnaire distributed using google forms. Based on the results of the research, several problems were found, namely unattractive teaching materials, technological stuttering and availability of facilities, fear of starting, copy paste culture, and learning assessment. These problems certainly require solutions, including: preparing interesting teaching materials, providing technological facilities, and using portfolio assessment.